An observational study to find out the etiological factors of Medoroga: A Nidanatmaka survey - Balendra Singh; Ritisha Verma; Pawankumar Godatwar (Wolters Kluwer Medknow Publications, 2022)
Introduction: With the advancements in the area of science and technology, today's people are living sedentary life style which emerges as a cause for life-threatening metabolic disorders such as obesity, hypertension, diabetes mellitus, atherosclerosis, and dyslipidemia. These metabolic diseases are the consequence of various etiological factors such as excessive food intake, day sleep, sedentary life style, excessive happy state of mind, and hereditary involvements. These metabolic disorders can be correlated with Medoroga, the diseases of Medovaha Srotasa in Ayurveda. Abnormal accumulation of Meda Dhatu in the body is known as Medodushti which includes several numbers of other Medovikara, collectively known as Medoroga. Methods: A Nidanatmaka survey was done among 500 subjects of Medoroga visiting outpatient and inpatient department of institute from January 2018 to March 2019. A structured questionnaire was given to each patient to collect data on sociodemographic profile, Ahara-satmya (dietary pattern), Vihara, and other Ayurvediya variables. Results: Maximum subjects of Medoroga were of age group 18-30 years (45.4%), male (67.6%), Hindu (88.6%), married (66.8%), graduates (69.8%), and belonged to upper middle class (74.6%) and Jangala Desha (95.8%). 57.2% subjects were vegetarians and gave the history of Akalabhojana (33.6%). Among total 500 subjects, 50.8% had Mandagni and were taking Madhura dominant Rasa in diet (49.6%). Nearly 56.8% of subjects were following sedentary lifestyle. It was also found that maximum subjects had body mass index in between 25 and 27.9 kg/m2 (36.4%) and waist/hip ratio in between 0.96 and 1.05 (95.2%). Conclusions: In the study, it was found that the person indulged in Ati-bhojana Sevana, Ati-gurvadi Sevana, Ati-madhura, Ati-sheeta-snigdhadi Ahara, and excessive intake of junk food, beverages like tea/coffee are more susceptible to Medoroga. Vihara such as Asyasukha, Avyayama, Diva-svapna, Achinta, and Nitya-harsha were also proved to be etiological factors of Medoroga.